2020
DOI: 10.1177/0300060520934635
|View full text |Cite
|
Sign up to set email alerts
|

DPP-4 inhibition resembles exercise in preventing type 2 diabetes development by inhibiting hepatic protein kinase Cε expression in a mouse model of hyperinsulinemia

Abstract: Objective Interventions for hyperinsulinemia (HINS), an early indicator of type 2 diabetes mellitus (T2DM), can significantly reduce the T2DM risk. This study aims to determine how dipeptidyl peptidase-4 (DPP-4) inhibition prevents HINS progression to T2DM through ameliorating hepatic steatosis. Methods KKay mice were used as a HINS model and they underwent exercise or received a DPP-4 inhibitor, MK0626. Hepatic steatosis was examined and liver diacylglycerol levels were determined. Human hepatic cells (LO2) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Hepatic dysfunction is known to contribute to the development of metabolic disorders, emphasizing the pivotal role of the liver in energy metabolism [ 19 ]. HFD increases lipid accumulation in the liver which can contribute to hyperinsulinemia and NAFLD [ 2 , 3 ]. ACSL3, a member of the ACSL family in lipid droplets, is known to play a role in DNL in the liver [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hepatic dysfunction is known to contribute to the development of metabolic disorders, emphasizing the pivotal role of the liver in energy metabolism [ 19 ]. HFD increases lipid accumulation in the liver which can contribute to hyperinsulinemia and NAFLD [ 2 , 3 ]. ACSL3, a member of the ACSL family in lipid droplets, is known to play a role in DNL in the liver [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, exercise can transiently decrease hepatic lipid levels by increasing fatty acid (FA) uptake and β-oxidation in muscles, and thus hepatic lipid storage can be reversed after prolonged exercise training (EX). Combined, previous studies suggest the beneficial effect of exercise on diacylglycerol (DAG) accumulation in the liver [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, dipeptidyl peptidase-4 (DPP-4), which is highly expressed in the liver, is a type of transmembrane peptidase that inhibits type 2 DM [ 33 ]. DPP-4 inhibition potentially improves hepatic steatosis and insulin resistance, similar to exercise [ 34 , 35 ]. Our data confirmed that the active compound network in SC helps regulate DDP-4 expression.…”
Section: Discussionmentioning
confidence: 99%